The application of tDCS in psychiatric disorders: a brain imaging view. (1st January 2016) - Baeken, Chris; Brunelin, Jerome; Duprat, Romain; Vanderhasselt, Marie-Anne
Abstract : Background: Transcranial direct current stimulation (tDCS) is a non-invasive, non-convulsive technique for modulating brain function. In contrast to other non-invasive brain stimulation techniques, where costs, clinical applicability, and availability limit their large-scale use in clinical practices, the low-cost, portable, and easy-to-use tDCS devices may overcome these restrictions. Objective: Despite numerous clinical applications in large numbers of patients suffering from psychiatric disorders, it is not quite clear how tDCS influences the mentally affected human brain. In order to decipher potential neural mechanisms of action of tDCS in patients with psychiatric conditions, we focused on the combination of tDCS with neuroimaging techniques. Design: We propose a contemporary overview on the currently available neurophysiological and neuroimaging data where tDCS has been used as a research or treatment tool in patients with psychiatric disorders. Results: Over a reasonably short period of time, tDCS has been broadly used as a research tool to examine neuronal processes in the healthy brain. tDCS has also commonly been applied as a treatment application in a variety of mental disorders, with to date no straightforward clinical outcome and not always accompanied by brain imaging techniques. Conclusion: tDCS, as do other neuromodulation devices, clearly affects the underlying neuronal processes. However, research on these mechanisms in psychiatric patients is rather limited. A better comprehension of how tDCS modulates brain function will help us to define optimal parameters of stimulation in each indication and may result in the detection of biomarkers in favor of clinical response.